Comunicación virtual y su incidencia en el comportamiento de los adolescentes del sector el recreo en la Parroquia San Camilo del cantón Quevedo, año 2022 - Contreras Chacon, Mariuxi Gabriela (2022)
The current technological tools offer various advantages of being able to be communicated, and informed of everything that happens, it is the responsibility of society that it be put to good use, virtual communication is one of the best resources that we currently have, it allows send messages immediately, free and simultaneously sending the same messages at the same time which saves time and resources for users, this research aims to determine virtual communication and its impact on the behavior of adolescents in the El Recreo sector in the San Camilo parish, of the Quevedo canton, for which the survey was applied as a technique for data selection, for which a questionnaire of questions was elaborated in relation to the subject of study, concluding that virtual communication is an excellent resource that provides the technology to be informed quickly and in a timely manner, breaking down the barriers of time and space is necessary r of society to make correct use of the functions that are provided, through this tool that is available to everyone.